Chemical grouting Revised and expanded - Karol, Reuben H (Civil engineering, 1990)
Chapters include The Grouting Medium, Grouting Theory, Chemical Grouts, Grouting Technology, Field Equipment, Field procedures and tests, Grouting to Shut off seepage, Grout curtains, Grouting for Strength, Grouting in Tunnels and Shafts, Special applications of chemical grouts, Specifications, supervision and inspection, Grouting Research. Also Appendices about Microfine cements, Glossary of terms, Computer program, Tunnel Design criteria, Suggested test method for determining strength of grouted soils for design, Government publications.